On the relationship between myth and fiction: an approach based on aranda (australian aboriginal) ethnography (Colloquia Comparativa Litterarum, 2025)
The author adopts a comparative cultural perspective in order to grasp the social role played by fiction in contemporary Western societies. As Jean-Marie Schaeffer reminds us, fictional competence stems from a child’s early interactions with care-givers. However, cross-cultural studies have identified significant structural differences in how these interactions take place. The author relates these differences to the divergent modes of sociability obtaining in two types of cultural contexts: present-day Western societies in which literary traditions have become central on the one hand, and societies with an oral tradition on the other. The current role of fiction in the West is compared with the processes at play in the creation of mythical narratives among the Aranda, an Aboriginal population of Central Australia. The author shows that whereas both mythological accounts and fictional works are cultural products made to be shared, the form this pooling of knowledge takes, and the functions associated with it, are closely connected with the modes of relational mediation characteristic of the society concerned.
Keywords: Myth; Fiction; Early childhood interactions; Australian Aborigines; Aranda; Transitional space; Transitional object; Dreaming; Cosmology; Ritual